PERISTILAHAN PENGOBATAN TRADISIONAL “BARAI” PADA MASYARAKAT DAYAK BEKAMBAE - Yenni Astuti; Hotma Simanjuntak; Agus Syahrani (Universitas Tanjungpura, 2021)
AbstractThis study aims to describe the terminology of traditional medicine 'Barai' in the Bekambae Dayak community. This study mainly discussed the terminology, the word class, lexical meaning, grammatical meaning, cultural meaning, and implementation of traditional medicine 'Barai' on the Bekambe Dayak community towards teaching and learning instruction. The method used in this research is descriptive in the form of qualitative. Data collection techniques applied were observation, interview, note-taking, and recording. Overall, 152 data on the terminology of traditional medicine 'Barai' in the Bekambae Dayak community consist of 8 data in terms of tools, 25 data on materials, 23 data on cultural objects, 6 data on disease names, 5 data on perpetrators, 11 data on taboo terms, and 74 data on stages. The word class consists of 57 data on monomorphemic, 7 data on polymorphemic, 30 data on phrases, 18 data on compound words, and 2 data on reduplication. The meanings contained in the terminology of traditional medicine 'Barai' in the Bekambae Dayak community consist of 152 data on lexical, 40 data on grammatical, and 148 data on cultural meanings. The results of the research were implemented into the Indonesian language instruction in the form of a descriptive text.Keywords: Terminology, Traditional Medicine, Barai, Bekambae Dayak Community.